STRUCTURAL AND ELECTRICAL-PROPERTIES OF BATIO3 GROWN ON P-INP (100) BY LOW-PRESSURE METALORGANIC CHEMICAL-VAPOR-DEPOSITION AT LOW-TEMPERATURE - KIM, TW; YOM, SS (AMER INST PHYSICS, 1994)
Metalorganic chemical vapor deposition of BaTiO3 using Ba(tmhd)2, Ti(OC3H7)4, and N2O via pyrolysis at relatively low temperature (approximately 300-degrees-C) was performed in order to produce high-quality BaTiO3/p-InP (100) interfaces and BaTiO3 insulator gates with dielectric constants of high magnitude. Scanning electron microscopy showed that the surfaces of the BaTiO3 films had very smooth morphologies. Auger electron spectroscopy measurements showed that the compositions of the as-grown films consisted of barium, titanium, and oxygen. Transmission electron microscopy showed that the BaTiO3 films had interdiffusion and local epitaxial formations near the BaTiO3/p-InP (100) interfaces. Room-temperature current-voltage and capacitance-voltage (C-V) measurements clearly revealed metal-insulator-semiconductor behavior for the BaTiO3 insulator gates, and the interface state densities at the BaTiO3/p-InP interfaces were approximately low 10(11) eV-1 cm-2 at an energy about 0.6 eV below the conduction-band edge. The dielectric constant of the BaTiO3 thin film determined from C-V measurements was as large as 78. (C) 1994 American Institute of Physics.
Keywords: THIN-FILMS; OXIDE; SI